Archiviolithic: The Anthropocene and the Hetero-Archive. Issue 1 (May 2014) - Colebrook, Claire
<x xml:space="preserve">Abstract</x> This essay explores three deconstructive concepts – archive, anthropocene, and auto-affection – across two registers. The first is the register of what counts as readability in general, beyond reading in its narrow and actualized sense. (This would include the reading of non-linguistic systems and traces, including the stratigraphic reading of the planet earth's sedimented layers of time that are archived in the geological record, and the reading of human monuments ranging from books to buildings). The second register applies to Derrida today, and what it means to read the corpus of a philosopher and how that corpus is governed by (and governs) proper names. I want to suggest that the way we approach proper names in philosophy and theory is part of a broader problem of our relation to what it is to read, and how readability intertwines with the human.